2019
DOI: 10.1002/hyp.13677
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land surface temperatures on suprapermafrost groundwater on the central Qinghai‐Tibet Plateau

Abstract: To investigate the influences of land surface temperatures (LSTs) on suprapermafrost groundwater discharge, a river valley was selected in a typical permafrost region of Fenghuoshan (FHS) watershed on the central Qinghai‐Tibet Plateau. We developed a two‐dimensional model to simulate the suprapermafrost groundwater seasonal dynamics controlled by LSTs and the changing trends under a warming climate scenario (3°C/100 year). We calibrated key parameters of our model by the field observations at FHS watershed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The SUTRA model simulations indicated that groundwater provides significant contributions to streams in the form of baseflow and that the majority of groundwater flow is from the shallow aquifer above the permafrost. Huang et al (2019) used the FEFLOW hydrogeological software program to simulate supra-permafrost groundwater discharge in different land surface temperature conditions on the central QTP. They found that topography, particularly aspect, plays an essential role in temperature, permeability, and groundwater discharge.…”
Section: Permafrost Groundwater Modelsmentioning
confidence: 99%
“…The SUTRA model simulations indicated that groundwater provides significant contributions to streams in the form of baseflow and that the majority of groundwater flow is from the shallow aquifer above the permafrost. Huang et al (2019) used the FEFLOW hydrogeological software program to simulate supra-permafrost groundwater discharge in different land surface temperature conditions on the central QTP. They found that topography, particularly aspect, plays an essential role in temperature, permeability, and groundwater discharge.…”
Section: Permafrost Groundwater Modelsmentioning
confidence: 99%
“…Many cold‐region surface processes, such as snow cover insulation, snow redistribution, shifts in vegetation, differential radiation due to slope aspect, turbulent fluxes, and seasonally variable albedo, significantly impact the ground thermal and hydrologic conditions (Jorgenson et al, 2010; Shur & Jorgenson, 2007; Young, Lemieux, Delottier, Fortier, & Fortier, 2020). Depending on the setting, some of these processes strongly influence land surface temperatures (Goodrich, 1982; Zhang, 2005), which in turn will impact the distribution of frozen ground and groundwater flow patterns (Connon, Devoie, Hayashi, Veness, & Quinton, 2018; Huang et al, 2020; Kurylyk, MacQuarrie, & McKenzie, 2014; Qi et al, 2019). For example, O'Neill and Burn (2017) found that a talik had formed underneath a snow fence in continuous permafrost, which led to half a meter of land subsidence.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Most of the studies that use these models have considered archetypical cold hydrogeological environments, with the objective of developing a conceptual understanding of these complex settings and how they respond to warming (e.g., Bense et al, 2012; Frampton, Painter, & Destouni, 2013). Research efforts to date have highlighted the importance of heat advection through groundwater flow as a possible contributor to permafrost degradation in certain settings (Dagenais, Molson, Lemieux, Fortier, & Therrien, 2020; McKenzie & Voss, 2013; Shojae Ghias, Therrien, Molson, & Lemieux, 2018; Sjöberg et al, 2016), elucidated the formation and hydrogeological impact of lateral and vertical taliks (Jafarov et al, 2018; Lamontagne‐Hallé, McKenzie, Kurylyk, & Zipper, 2018; Rowland, Travis, & Wilson, 2011; Wellman, Voss, & Walvoord, 2013), illustrated the current and future patterns of groundwater discharge to streams (Evans, Ge, Voss, & Molotch, 2018; Evans, Godsey, Rushlow, & Voss, 2020; Huang et al, 2020; Lamontagne‐Hallé et al, 2018), and to a very limited extent presented field applications of these models (e.g., Dagenais et al, 2020; Evans et al, 2020; Kurylyk, Hayashi, Quinton, McKenzie, & Voss, 2016; Langford, Schincariol, Nagare, Quinton, & Mohammed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In summer, the shallow ground thaws, and subsurface water is readily able to flow. Subsurface flow triggers heat advection that modifies ground temperatures, and the extent of this temperature change is a function of flow rates, hydrogeologic properties, and regional climate (McKenzie, Siegel, Rosenberry, Glaser, & Voss, 2007;Woo, 2012;Shojae Ghias, Therrien, Molson, & Lemieux, 2018;Huang et al, 2019;Shojae Ghias, Therrien, Molson, & Lemieux, 2018;Woo, 2012). Paquette, Fortier, and Vincent (2017) observed that in polar desert conditions, snowmelt water flowing through water tracks has a cooling effect on the subsurface and restricts the extent of active-layer deepening.…”
mentioning
confidence: 99%